Sistem Pendukung Keputusan Metode Technique For Order Preference By Similirity To Ideal Solution Untuk Menentukan Penerima Beasiswa Tidak Mampu Di SMK Negeri 1 Bintan Timur - Hendi Setiawan; Fikri Haiqal (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
This research is motivated by the condition of the problem of poverty which is the center of attention and problems in every educational institution, especially SMK Negeri 1 Bintan Timur. Government programs that are used to reduce poverty reduce the burden on students in meeting the needs of school fees, one of which is the scholarship assistance program for the poor at SMK Negeri 1 Bintan Timur. The purpose of this study is to assist the school in determining the distribution of the scholarship program for the poor to SMK Negeri 1 Bintan Timur with a decision support system. One of the methods in making decisions is the technique for others preference by similirity to ideal solution or commonly abbreviated as the topsis method. Topsis is a multi-criteria decision-making method that was first introduced by Yoon and Hwang (1981). Topsis uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view by using Euclidean distance to determine the relative proximity of an alternative to the optimal solution. This research using the Topsis method was conducted to determine who will receive scholarship assistance for underprivileged students at SMK Negeri 1 Bintan Timur in accordance with the requirements or criteria that have been determined. the results of the study can help SMK Negeri 1 Bintan Timur to select prospective scholarship recipients based on scholarship criteria with computerized data. The results of the development of this system, can help the distribution of scholarship assistance at SMKN 1 Bintan Timur on target to be given to students who are less fortunate and deserve assistance by looking at the results of the assessment in the form of a report form.